Clopidogrel in non-ST segment elevation acute coronary syndromes: an overview of the submission by the British Cardiac Society and the Royal College of Physicians of London to the National Institute for Clinical Excellence, and beyond. Issue 9 (15th August 2005) - Walsh, S J; Spence, M S; Crossman, D; Adgey, A A J
Abstract : A comprehensive appraisal was undertaken on behalf of the British Cardiac Society and the Royal College of Physicians of London to assess the use of clopidogrel in acute coronary syndromes. The appraisal was submitted to the National Institute for Clinical Excellence (NICE) in August 2003 and contributed to the development of the recently published guidelines for the use of clopidogrel in acute coronary syndromes. The submission to NICE and more recent publications evaluating the use of clopidogrel are reviewed.